Coke management: unveiling the role of Ce substitution in Gd2Zr1.8Ni0.2O7-δ catalyst for dry reforming of methane - Ghodke, Seema R.; Mule, Harshada M.; Bhatkar, Akash; Devi, R. Nandini (Energy & Fuels, 2025)
The redox characteristics of cerium have become crucial elements in the carbon gasification process during methane dry reforming. This work examines the effect of cerium substitution in the Gd2Zr1.8Ni0.2O7-delta catalyst during methane dry reforming, employing a range of Ce-substituted Gd2Zr1.8-x Ni0.2Ce x O7-delta (x = 0.1, 0.2, 0.5, 0.75) catalysts synthesized via the citrate gel method. The materials crystallized in a fluorite structure, as verified by X-ray diffraction analysis and Raman spectroscopy. Enhanced reducibility of the substituted catalysts was assessed through H2-temperature-programmed reduction analysis. CO2 and O2 desorption studies along with X-ray photoelectron spectroscopy validated the enhanced basicity and generation of active oxygen and hydroxyl species. The enhanced activity and coke gasification in Gd2Zr1.6Ni0.2Ce0.2O7-delta catalyst are attributed to surface hydroxyl species, and prominent intermediate carbonate and bicarbonate species were further verified by in situ infrared spectroscopy. The high basicity of the Gd2Zr1.6Ni0.2Ce0.2O7-delta catalyst and high concentrations of oxygen vacancies (similar to 66.4%) enhances CO2 adsorption and desorption, resulting in continuous CO2 activation, leading to less carbon formation and superior activity of the catalyst. The Gd2Zr1.6Ni0.2Ce0.2O7-delta catalyst exhibits the highest CH4 and CO2 conversion rates, at 85% and 93.5%, respectively, and remains stable for 100 h. Postreaction analysis of Gd2Zr1.6Ni0.2Ce0.2O7-delta confirms structure stability and less carbon formation compared to other substituted catalysts in dry reforming of methane. This study demonstrates that the moderate concentration of Ce in the Gd2Zr1.6Ni0.2Ce0.2O7-delta catalyst exhibits balanced activity and coke gasification capacity in the dry reforming of methane for a longer duration.